Growth and convergence in the Central and East European countries towards EU (1992-2002) - Aleksandar Vasilev (Eastern Journal of European Studies, 2015)
The main focus of the paper is the growth process in transition countries in the period 1992-2002, by using the production function approach. The empirical cross-section study performed found that initial life expectancy and net savings speed up growth while death rate, inflation, and terms of trade hamper the increase in GDP. The paper also aims at providing policy implications, e.g. better spending in the legal system, healthcare and social security could help governments foster the restructuring process and decrease the effect of the mistakes made in the past.
Keywords: E01; 330; growth; transition countries